Agricultural Education Model Through Coffee Agrotourism at Sapit Farm: (Case Study in Sapit Village, East Lombok, NTB) - Asasandi, I Gusti Ngurah Aryawan (UNIMUS Web Conferences, 2025)
The purpose of this study is to: (1) find out in detail the ins and outs of coffee agrotourism run by the “Sapit Farm” agrotourism in increasing tourist knowledge of coffee farming. (2) Find out the economic impacts caused by farming integrated with tourism, namely coffee agrotourism, with the example in this study being the “Sapit Farm” Agrotourism. This study uses a case study method by focusing on an in-depth study related to the “Sapit Farm” agrotourism, which is one way of approaching agricultural education for tourists who want to learn more about coffee agribusiness. The study yielded the following results: run by the "Sapit Farm" Agrotourism in Sapit Village is very effective in increasing participants’ knowledge in understanding coffee farming. (2) In terms of income, the management of the "Sapit Farm" Agrotourism has received significant profits with income of up to Rp. 120,000,000 per year from the coffee bean harvest and the sale of seeds amounting to Rp. 75,000,000 per year.